2020
DOI: 10.1093/mnras/staa1348
|View full text |Cite
|
Sign up to set email alerts
|

Stability of Jovian Trojans and their collisional families

Abstract: The Jovian Trojans are two swarms of objects located around the L4 and L5 Lagrange points. The population is thought to have been captured by Jupiter during the Solar system’s youth. Within the swarms, six collisional families have been identified in previous work, with four in the L4 swarm, and two in the L5. Our aim is to investigate the stability of the two Trojan swarms, with a particular focus on these collisional families. We find that the members of Trojan swarms escape the population at a linear rate, … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
59
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(67 citation statements)
references
References 104 publications
5
59
0
Order By: Relevance
“…The fraction of survivors for each small body population and for different T ML is shown in Figure 2. Overall, while the MBAs and TNOs are mostly stable with no more than a few per cent lost, 40% of the JTAs are removed during the ML phase; and we confirm that JTAs in the leading L4 cloud are more resistant by a few per cent than the trailing L5 cloud, in agreement with Di Sisto et al (2014); Holt et al (2020) (this phenomenon is also observed during the WD phase). Also, in the three simulations with different T ML and most apparently for the JTAs, it seems that when time is measured against the respective T ML , the small objects tend to be lost at the same time, i.e., when the planet-star mass ratio attains some certain value.…”
Section: Mass Loss Phasesupporting
confidence: 81%
See 2 more Smart Citations
“…The fraction of survivors for each small body population and for different T ML is shown in Figure 2. Overall, while the MBAs and TNOs are mostly stable with no more than a few per cent lost, 40% of the JTAs are removed during the ML phase; and we confirm that JTAs in the leading L4 cloud are more resistant by a few per cent than the trailing L5 cloud, in agreement with Di Sisto et al (2014); Holt et al (2020) (this phenomenon is also observed during the WD phase). Also, in the three simulations with different T ML and most apparently for the JTAs, it seems that when time is measured against the respective T ML , the small objects tend to be lost at the same time, i.e., when the planet-star mass ratio attains some certain value.…”
Section: Mass Loss Phasesupporting
confidence: 81%
“…Those objects are slowly diffusing, transversing various resonances and increasing eccentricity and inclination, causing close encounters with Jupiter and escape from the Trojan region (Robutel & Gabern 2006;Di Sisto et al 2019). The escape fraction from the L5 swarm is somewhat higher than that from L4 (Di Sisto et al 2014;Holt et al 2020). Lying in the immediate vicinity of Jupiter, the chance of collisions between the escaped JTAs with that planet becomes non-negligible, almost as frequent as that of reaching the WD Roche radius (Di Sisto et al 2019).…”
Section: White Dwarf Phasementioning
confidence: 99%
See 1 more Smart Citation
“…This is not unexpected since the dynamics around the L5 point is a mirror image of the L4 point in the restricted three-body problem. Furthermore, as noted in Section 1 and some other previous works (Nesvorný & Dones 2002;Di Sisto et al 2014;Holt et al 2020), under the gravitational effects of the four outer planets, the L4 and L5 Trojan swarms show almost the identical dynamical structure and stability in the long-term evolution. We thereby will only consider the L4 Jupiter Trojans in the following sections.…”
Section: Theoretical Approachsupporting
confidence: 73%
“…In this section, we still adopt the present outer solar system model, consisting of the Sun and four giant planets (i.e., Jupiter, Saturn, Uranus and Neptune). As in recent dynamical explorations of the Jupiter Trojans (e.g., Hellmich et al (2019), Holt et al (2020)), to construct robust simulations, we follow the long-term evolution of 30,000 test Trojans around the L4 point. Initially, all particles have the same semimajor axis (a ≈ 5.2 AU) with Jupiter.…”
Section: Apsidal Clustering: Reproductionmentioning
confidence: 99%